Assessment of the seismic safety of school buildings in Mexico: A first look. Issue 2 (December 2020) - Alcocer, Sergio M; Arce, José C; Murià-Vila, David; Fernández-Sola, Luciano R; Guardia, Daniel A
For the first time in Mexico, a comprehensive data gathering and analysis project on the seismic performance of school buildings in the aftermath of the 2017 earthquakes was developed. Aimed at supporting the planning and decision-making of the Mexican government's reconstruction program, school performance was observed and measured in the field. To further evaluate building performance, numerical modeling of archetypical buildings was carried out. Calculated performance was consistent with observed structural damage. Numerical analysis indicated that pre-1985 masonry and concrete buildings are more likely to exhibit damage that could compromise the structural stability. In contrast, recent structures are very likely to attain the immediate occupancy (IO) performance level that is implicitly assumed in school design. Studies indicated that rehabilitated school buildings through wall jacketing in masonry buildings and by adding new concrete shear walls and masonry infills to concrete structures are likely to comply with IO. From the lessons learned, policy, technical, implementation, and sustainability and outreach recommendations are proposed to implement a multiannual, systematic, incremental, and integral strategy for reducing earthquake risk of school buildings in Mexico.